THE RELATIONSHIP BETWEEN ULTRA-PROCESSED (UPF) AND CARDIOVASCULAR DISEASE AMONG ADULT: A SCOPING REVIEW - Sitasari, Almira; Putri, Qorina Rizkia; Wulandari, Adinda Maesa; Siswati, Tri; Wijanarka, Agus (Mandala Of Health, 2025)
Background: The global increase in ultra-processed food (UPF) consumption has raised significant public health concerns due to its association with cardiovascular disease (CVD). UPFs are typically high in sodium, saturated fats, added sugars, and artificial additives, which contribute to metabolic disturbances and increase CVD risk. This scoping review aims to synthesize the current evidence on the relationship between UPF consumption and CVD risk in adults. Methods: A systematic search was conducted using PubMed and Google Scholar for studies published between 2019 and 2024. Eligible studies included observational research assessing UPF consumption and its impact on cardiovascular health. A total of 172 articles were initially identified, and after applying inclusion criteria, nine relevant studies were selected for review. Results: The findings consistently indicate that high UPF consumption is linked to an increased risk of hypertension, obesity, dyslipidemia, and elevated triglyceride levels—key contributors to CVD. Several studies also highlight a significant association between frequent UPF intake and higher rates of cardiovascular mortality, particularly among high-risk populations. Conversely, diets rich in minimally processed foods, such as whole grains, fruits, and vegetables, demonstrate protective effects against CVD. Conclusions: There is a strong positive correlation between UPF consumption and heightened CVD risk. Public health interventions should focus on reducing UPF intake while promoting healthier dietary patterns to mitigate cardiovascular disease burden. Further longitudinal studies are needed to explore the long-term effects of UPF consumption on cardiovascular health